Analisis Hasil Asesmen Diagnostiksebagai Dasar Pelaksanaan Pembelajaran Berdiferensiasi Di Sekolah Dasar - Muhamad Alfarisi (LAMBDA : Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2024)
Students have different characteristics and a diversity of learning needs. Educators need to map students' learning needs according to students' learning abilities, interests and learning talents. Cognitive and non-cognitive diagnostic assessments make it easier for teachers to map students' learning needs through tests or expanded questionnaires. Diagnostic assessments are carried out with the aim of reviewing students' initial abilities in learning readiness. So it can be a solution in applying differentiated learning. The purpose of this observation is to analyze the number of diagnostic assessments as a benchmark for differentiated learning for Pancasila Education subjects in class IV. The research method used is descriptive qualitative. This data was collected using non-participatory observation from carrying out cognitive diagnostic assessment tests. Data analysis techniques use the Milles and Huberman models, including value reduction, data presentation and drawing conclusions. Research in class IV A. The results of the research show that educators have mapped groups based on students' learning readiness using cognitive diagnostic assessment tests. Groupings are made from developing, and advanced groups. Content differentiated learning can be applied to provide learning material based on proficiency level so that students' learning needs are met.